Narrative Influences on "Desire to Act in My Community" in Digital Storytelling Workshops for Latina Teens. (April 2018) - Larkey, Linda; Del Toro-Mejías, Lizbeth; DiFulvio, Gloria; Gubrium, Aline
Digital storytelling workshops are increasingly being used to capture lived experiences and develop/disseminate health promotion messages for vulnerable and marginalized populations. Thirty female Latina teens of varied sexual/parity status produced digital stories of significant life experiences in a group context and then viewed and evaluated them using the Narrative Quality Assessment Tool. This tool was used to examine participants' experience of emotional engagement and identification with each story as well as a single-item indicator of desire to "do something in my community" related to the story. Emotional engagement was moderately strong; identification scores were neutral relative to the stories. Emotional engagement was strongly, significantly related to "desire to act in my community, " while identification was not related. Emotional engagement should be considered an important factor to incorporate in the production of digital stories for purposes of developing interest in social action beyond the digital storytelling workshop.